Sosialisasi Airfield Lighting System (AFL) berbasis Virtual Tour sebagai Alat Bantu Pendaratan Visual di Bandar Udara bagi Siswa SMA/SMK - Lubis, Ukkasyah Sabbit Aqdamana; Kona, Musri; Bunahri, Rifqi Raza (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2024)
Airfield Lighting System (AFL) also known as Aeronautical Ground Lighting (AGL) is a term used at airports to assist and serve pilots visually using various types of lights when aircraft take off, land, and taxi to move efficiently and safely. This research uses qualitative research to obtain results regarding the benefits of learning a virtual tour-based visual landing aid system for high school students in Jayapura. Introduction to Airfield Lighting System (AFL) is very useful because aircraft runways are very important for the safety of transportation users, especially in terms of commercial flights. The use of aircraft runways is not only during the day but also at night for landing and releasing aircraft. The introduction of an Airfield Lighting System (AFL) based on virtual tour as an information medium for visual landing aids at the airport for high school students in Jayapura also has benefits for local high school students as a medium of information and increased understanding of visual landing aids at the airport